Comparison of microdilution and agar dilution procedures for testing antibiotic susceptibility of Neisseria gonorrhoeae. - Shapiro, M A (1984)
Studies were run in parallel to compare the broth microdilution method and the chocolate agar dilution method for testing antibiotic susceptibility of Neisseria gonorrhoeae. Six clinically relevant drugs were tested against 23 clinical isolates of N. gonorrhoeae, including several penicillinase-producing, as well as multiply resistant, strains. Results showed that the MIC obtained by the two methods were not significantly different. The microdilution method appears to be a more sensitive system for discriminating penicillinase activity. The microdilution system is a more expedient method for screening new antibacterial agents and is more readily adaptable to new automated equipment.